2017
DOI: 10.4236/acs.2017.74038
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Analysis of Rainfall and Temperature Extreme Indices in Tanzania

Abstract: Climate extreme indices in Tanzania for the period 1961-2015 are analyzed using quality controlled daily rainfall, maximum and minimum temperatures data. RClimdex and National Climate Monitoring Products (NCMP) software developed by the commission for climatology of the World Meteorological Organization (WMO) were used for the computation of the indices at the respective stations at monthly and annual time scales. The trends of the extreme indices averaged over the country were computed and tested for statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 16 publications
(3 reference statements)
3
24
0
Order By: Relevance
“…In East African countries, climate change has already affected weather patterns and hydrological cycles. Several studies over East Africa region indicated that temperatures have increased, rainfall in particular, the long rains that are historically considered important for agriculture activities in the region have declined by later onset and earlier cessation (Wainwright et al, 2019;Borhara et al, 2020), the frequency and intensity of extreme weather events such as persistent drought and floods have increased (Kijazi and Reason, 2009a,b;Chang'a et al, 2017;Nicholson, 2017), the unpredictability of rainfall seasons has increased, and sea rise and coastal erosion have been noticed over many coastal regions (Tumbo et al, 2010;Liwenga et al, 2014;Mubaya et al, 2014). These events have affected water availability, food security, human health, and other socioeconomic livelihoods (Opiyo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In East African countries, climate change has already affected weather patterns and hydrological cycles. Several studies over East Africa region indicated that temperatures have increased, rainfall in particular, the long rains that are historically considered important for agriculture activities in the region have declined by later onset and earlier cessation (Wainwright et al, 2019;Borhara et al, 2020), the frequency and intensity of extreme weather events such as persistent drought and floods have increased (Kijazi and Reason, 2009a,b;Chang'a et al, 2017;Nicholson, 2017), the unpredictability of rainfall seasons has increased, and sea rise and coastal erosion have been noticed over many coastal regions (Tumbo et al, 2010;Liwenga et al, 2014;Mubaya et al, 2014). These events have affected water availability, food security, human health, and other socioeconomic livelihoods (Opiyo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These two decades are known to be the driest decades over the study domain. Dry conditions were also recorded in neighboring countries specifically Rwanda and Tanzania (Ngarukiyimana et al 2017b;Chang'a et al 2017;Idrissa F. Nkurunziza et al 2019). As shown in the figure, the fluctuations over a 1-month time scale between wet and dry conditions are difficult to depict.…”
Section: Evaluation Of Drought Patterns On Annual and Seasonal Scalesmentioning
confidence: 96%
“…Thereafter, the SQMK results showed that more rainfall fluctuations started from the 1990s decade, a period coinciding with the first abrupt point of forward and backward sequential statistic. The 1990s decade was also identified to be the starting period of an increasing in rainfall variability resulting in more extremes weather events across East Africa Ngarukiyimana et al 2017c;Chang'a et al 2017; It was found that more abrupt points occurred after the year 2005. However, according to previous SPI time series analyses, it was found that more dry events occurred within the period 1993-2005.…”
Section: Spatial Trend Analyses Of Annual and Seasonal Drought With Smentioning
confidence: 99%
“…The evaluation has been conducted for 17 years ranging from 2000 to 2016. The choice of studying the period 2000–2016 is motivated by the fact that this period is found to record more extreme weather events not only over Burundi but also over East Africa in general (Ongoma et al, ; Chang'a et al, ; Ngarukiyimana et al, ; Nkunzimana et al, ). Therefore, an evaluation on daily scale for this period is of more concern.…”
Section: Daily Assessment Of Chirps and Persiann‐cdrmentioning
confidence: 99%